Developmental Trends of Visual Processing of Letters and Objects Using Naming Speed Tasks - Easson, Kaitlyn; Al Dahhan, Noor Z.; Brien, Donald C.; Kirby, John R.; Munoz, Douglas P. (Frontiers in Human Neuroscience, 2020)
Studying the typical development of reading is key to understanding the precise deficits that underlie reading disabilities. An important correlate of efficient reading is the speed of naming arrays of simple stimuli such as letters and pictures. In this cross-sectional study, we examined developmental changes in visual processing that occurs during letter and object naming from childhood to early adulthood in terms of behavioral task efficiency, associated articulation and eye movement parameters, and the coordination between them, as measured by eye-voice span in both the spatial and temporal domains. We used naming speed (NS) tasks, in which participants were required to name sets of letters or simple objects as quickly and as accurately as possible. Single stimulus manipulations were made to these tasks to make the stimuli either more visually and/or phonologically similar to one another in order to examine how these manipulations affected task performance and the coordination between speech and eye movements. Across development there was an increased efficiency in speech and eye movement performance and their coordination in both the spatial and temporal domains. Furthermore, manipulations to the phonological and visual similarity of specific letter and object stimuli revealed that orthographic processing played a greater role than phonological processing in performance, with the contribution of phonological processing diminishing across development. This comprehensive typical developmental trajectory provides a benchmark for clinical populations to elucidate the nature of the cognitive dysfunction underlying reading difficulties.